I delitti contro il sentimento religioso: tra incriminazione dell’opinione e tutela della libertà di manifestazione del pensiero (Stato, Chiese e pluralismo confessionale, 2018)
SOMMARIO: 1. Premessa: il vilipendio quale “reato d’opinione” - 2. L’evoluzione dei delitti contro il sentimento religioso - 3. (segue): la riforma del 2006 - 4. La sentenza della Corte costituzionale n. 188 del 1975 - 5. L’esercizio del diritto di libera manifestazione del pensiero quale causa di giustificazione (art. 51 c.p.) - 6. Le più recenti applicazioni della giurisprudenza di legittimità - 7. Chiusa.Are the crimes against religious sentiment compatible with the exercise of freedom of expression?ABSTRACT: The crimes against religious sentiment, provided by the Italian Criminal Code, are mainly framed as “crimes of opinion”. Therefore, it should be ascertained whether and how those crimes are compatible with the exercise of freedom of expression, guaranteed as a fundamental right by Art. 21 of the Italian Constitution. The paper provides an overview of the jurisprudence – of ordinary courts and the Constitutional Court – and of the legislative evolution since 1930s about the crimes against religious sentiment.